Cooking in Baskets Using Hot Rocks - Jonathan Thornton (EXARC Journal)
Baskets are among the most ancient of human artefacts. Everyone is familiar with their most common functions as containers for transport and storage. When told that baskets have also served as cooking vessels, most people will be unable to conceive of how this is possible, yet this was a primary function of baskets for many cultures of the past, and some until the present. The surprising key to this method is in the use of hot rocks, which cook the contents of the basket quickly and efficiently without charring or damaging the container. Though baskets are discussed here, the technique is transferable to any organic container, including those made of bark and leather (Nelson 2010).